Порівняльний аналіз протоколів доказів із нульовим розголошенням - Прядко, В. С. (ХНУРЕ, 2024)
The article provides an overview of zero-knowledge proofs (ZKPs), emphasizing their role in ensuring privacy and data protection in technologies such as blockchain. It explains ZKP as a method that allows proving truth without revealing basic details, ensuring security in digital interactions. The text compares several ZKP protocols, including zk-SNARKs, zk-STARKs, Bulletproofs, and PLONK, highlighting their unique features, applications, and tradeoffs between efficiency, security, and privacy.The discussion reflects ZKP's ongoing development to overcome current limitations while offering a future in which privacy and verification are harmoniously integrated.
Keywords: Zero-Knowledge; протокол доказів